1984
DOI: 10.1111/j.1600-0870.1984.tb00240.x
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility of barotropic instability over northeast Brazil

Abstract: The easterly zonal wind profile over northeast Brazil during the rainy s e w n of a heavy rainfall year satisfies the necessary condition for the existence of barotropic instability. The wave with a wavelength of I250 km has the highest growth rate, 1.6 x s-I (e-folding time of about 6 days). The zonal wind profile is found to be stable during a dry year. This suggests that it is likely that barotropic instability might contribute to the interannual variations of rainfall over northeast Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A northward location of the ITCZ leads to drought in NEB. Earlier, Rao et al (1984) suggested a mechanism through which north-south displacement of the ITCZ changes the structure of lower atmospheric easterlies, leading to barotropic stability or instability. A more southerly position of the ITCZ, for example, causes barotropic instability of the easterly current, thus favouring rain-producing transient disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…A northward location of the ITCZ leads to drought in NEB. Earlier, Rao et al (1984) suggested a mechanism through which north-south displacement of the ITCZ changes the structure of lower atmospheric easterlies, leading to barotropic stability or instability. A more southerly position of the ITCZ, for example, causes barotropic instability of the easterly current, thus favouring rain-producing transient disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…A warm center in the Tropical North Atlantic and a cold center in the Tropical South Atlantic provokes a more northerly position of the Inter-Tropical Convergence Zone (ITCZ). A more northerly position of ITCZ reduces rainfall over NEB (Namais, 1972;Hastenrath and Heller, 1977;Marques et al, 1983;Rao et al, 1984). Also, a meridional (Hadley) circulation with rising motion over the Northern Atlantic and a sinking motion over the Southern Atlantic and the adjoining NEB develops causing a drought.…”
Section: Introductionmentioning
confidence: 99%